Project Based Learning: Pembuatan Motion Graphics “Affordable” untuk Klien LB LIA - Hidayat, Daffala Viro; Fami, Amata; Prayudo, Galih Ario; Mu'taz, Faris Afra (Jurnal Mahasiswa Kreatif, 2024)
Project-Based Learning (PjBL) is a learning approach where students learn by actively participating in real projects or tasks. This approach aims to prepare learners to face real-world situations and develop skills relevant to careers and everyday life. The (PjBL) approach was used in the creation of this motion graphics titled "Affordable" with the client LB LIA. The PjBL process involved planning, client needs analysis, conceptualization, production and evaluation. The results show that PjBL helps learners develop a deep understanding of graphic design and effective communication skills with clients. PjBL helped learners develop a deep understanding of graphic design and effective communication skills with clients. Although time management and communication challenges arose, collaboration between students and clients successfully overcame these obstacles so that this motion graphics project could run smoothly. With a focus on project-oriented learning, this article can serve as a guide for those interested in maximizing students' educational experience in the real world.